IMPLEMENTASI KEPEMIMPINAN STRATEGIS GUNA MENGHADAPI ANCAMAN BENCANA BANJIR DAN TSUNAMI DI PROVINSI KALIMANTAN TIMUR - Hayatul Khairul Rahmat; Hani Syarifah; Anwar Kurniadi; Rezki Masda Putra; Sri Wanda Wahyuni (Republic of Indonesia Defense University, 2021)
This study discusses the implementation of strategic leadership in dealing with the threat of tsunamis and floods in East Kalimantan Province. The research method used in this study is a qualitative research method with a library approach. The findings of this study are in the concept of strategic leadership, BPBD in regency or city level is a strategic leader who organizes disaster management in East Kalimantan Province. East Kalimantan Province consists of 7 regencies and 3 cities and according to the conditions in the field there are already 9 regencies/ cities that have BPBDs and one district does not yet have BPBDs, namely Mahakam Ulu Regency and assisted by BPBD Samarinda City. In implementing strategic leadership, what strategic leaders need to deal with floods and tsunamis is coordination between various stakeholders in disaster management and collaboration as a form of competence that must be possessed by strategic leaders. In a concrete sense, the activities carried out in dealing with floods in regencies/ cities in East Kalimantan Province have been running and tsunami monitoring is being carried out in collaboration with the Geophysics Station of BMKG of Balikpapan City.